Postural Orthostatic Tachycardia Syndrome as a Manifestation of Post-COVID-19 Syndrome - E. L. Trisvetova (Рациональная фармакотерапия в кардиологии, 2022)
The pandemic of coronavirus infection, the complex and insufficiently studied mechanisms of which cause disorders in the functions of many organs and systems of the body, has led to the emergence of new problems that are far from being resolved. Researchers note the difficulty in predicting the course of the disease and outcome due to the detection of many symptoms that arose at the height of the disease and persisted for 3-6 months after recovery. The term "post-COVID-19syndrome" has appeared, reflecting the condition of a patient who has undergone COVID-19, with a negative PCR test, and with symptoms lasting more than 12 weeks from the onset of the disease, which cannot be explained by an alternative diagnosis. Postural orthostatic tachycardia as a manifestation of the post-COVID-19syndrome has been described in young women who have undergone coronavirus infection of varying severity. In the case of the development of the syndrome of postural orthostatic tachycardia, the quality of life deteriorates, and the ability to work of patients is limited. There is no evidence base for drug therapy of postural tachycardia syndrome, in most cases empirical drug and non-drug methods of treatment are used.